PEMAHAMAN PLURALISME AGAMA BAGI PENYIAR AGAMA DALAM MEMBANGUN KERUKUNAN UMAT BERAGAMA - Ali Litiloly (IAIN Ambon, 2021)
This study aims to determine the importance of understanding religious pluralism for religious preachers in building harmony adherents of various religions. This research method used literature study while the technical analysis used descriptive technical analysis. Religious plurality is an empirical reality that is created outside of human authority (a necessity). This is what causes religious pluralism to become a historical reality that cannot be avoided from the reality of human life in many countries in the world including in Indonesia. In understanding religious pluralism, Alwi Shihab, John Hick and Faul Knitter agree that tolerance in religion is considerably needed to discover the human values that exist in each religion to induce the forming of harmony in religious communities. Therefore comprehending religious pluralism is important to be understood by all religious preachers so that the concepts of religious plurality and national plurality can be taken into account in determining subjects and methods of spreading religion either in the religious temples or in the community in order to avoid unrest and socio-religious conflict. Key word: Religious Pluralism, Religious Preacher, Religious harmony